2019
DOI: 10.1002/celc.201901586
|View full text |Cite
|
Sign up to set email alerts
|

Bottom‐Up Construction of Conjugated Microporous Polyporphyrin‐Coated Graphene Hydrogel Composites with Hierarchical Pores for High‐Performance Capacitors

Abstract: Three‐dimensional (3D) graphene hydrogel (GH) architectures are of great interest in applications towards electronics, environmental fields, catalysis devices, and sensors. However, due to the structure constraints of graphene, only macropore and low specific surface areas are obtained. Conjugated microporous polymers always possess a micro‐ and mesopore structure simultaneously, but the conductivity is very poor. However, both the conductivity and the pore parameter are important factors affecting the perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 26 publications
0
20
0
Order By: Relevance
“…According to the Brunauer‐Deming‐Deming‐Teller classification, the isotherms onto all of the gels can be defined as type V with H3 hysteresis loops, which are characteristic of mesoporous materials 43 . The hysteresis loops of the four gels at a relative pressure range of 0.8–1.0 indicated the presence of large mesopores and macrospores 44 . The Barrett–Joyner–Halenda (BJH) desorption pore diameter distribution of HAM, THAM‐1, THAM‐2, and THAM‐3 gels are shown in the Figure 3b, different pore sizes were observed in the four gels, and the pore size are mainly distribution in the range of 3.06–29.81 nm occurred which further indicating the existence of mesopores.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the Brunauer‐Deming‐Deming‐Teller classification, the isotherms onto all of the gels can be defined as type V with H3 hysteresis loops, which are characteristic of mesoporous materials 43 . The hysteresis loops of the four gels at a relative pressure range of 0.8–1.0 indicated the presence of large mesopores and macrospores 44 . The Barrett–Joyner–Halenda (BJH) desorption pore diameter distribution of HAM, THAM‐1, THAM‐2, and THAM‐3 gels are shown in the Figure 3b, different pore sizes were observed in the four gels, and the pore size are mainly distribution in the range of 3.06–29.81 nm occurred which further indicating the existence of mesopores.…”
Section: Resultsmentioning
confidence: 99%
“…43 The hysteresis loops of the four gels at a relative pressure range of 0.8-1.0 indicated the presence of large mesopores and macrospores. 44 The Barrett-Joyner-Halenda (BJH) desorption pore diameter distribution of HAM, THAM-1, THAM-2, and THAM-3 gels are shown in the Figure 3b, different pore sizes were observed in the four gels, and the pore size are mainly distribution in the range of 3.06-29.81 nm occurred which further indicating the existence of mesopores. In addition, the BET surface areas, total pore volume, and average pore diameters of HAM, THAM-1, THAM-2, and THAM-3 gels are listed in Table 1; the BET surface area of HAM, THAM-1, THAM-2, and THAM-3 were 1.836, 2.927, 11.821, 10.111 m 2 g −1 , total pore volume were 0.0023, 0.0051, 0.0641, 0.0398 cm 3 g −1 , and average pore diameters were 5.148, 6.974, 2.538, 2.167 nm, respectively.…”
Section: Porosity Analysismentioning
confidence: 94%
“…Compared with most previously reported hydrogel electrolyte-based supercapacitors, the Ragone plot of SPMA-ZHS exhibits a higher energy density of 164.13 Wh kg −1 at the power density of 1283.44 Wh kg −1 (Figure 3G, Table S2, Supporting Information). [52][53][54][55][56][57][58][59][60][61][62][63] Cycling performance is an important indicator for the supercapacitors. Cycling stability and coulombic efficiency of SPMA-ZHS were investigated at 10 A g −1 for 5000 charge-discharge cycles.…”
Section: Electrochemical Performancesmentioning
confidence: 99%
“…[8b] However, 3D graphene aerogel contains partially restacked graphene sheets, which still limits the maximum utilization of the graphene surface for polydopamine coatings. [14] The previous studies have shown that only graphene oxide (GO) precursor with high concentrations greater than 1 mg mL À 1 can be assembled into a 3D graphene hydrogel under hydrothermal conditions. [8b,15] Since the graphene hydrogel is assembled by partial restacking of the rGO sheets, a large fraction of the graphene surface is inaccessible to polydopamine coatings.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the polydopamine coated 3D graphene aerogel electrode exhibited a much higher capacity of ∼230 mAh g −1 in Li‐cells after the thermal annealing process, suggesting that graphene is a more effective substrate for utilizing the redox reactions of polydopamine compared to CNT [8b] . However, 3D graphene aerogel contains partially restacked graphene sheets, which still limits the maximum utilization of the graphene surface for polydopamine coatings [14] . The previous studies have shown that only graphene oxide (GO) precursor with high concentrations greater than 1 mg mL −1 can be assembled into a 3D graphene hydrogel under hydrothermal conditions [8b,15] .…”
Section: Introductionmentioning
confidence: 99%